The Drawbacks of Group Decision Making from a Psychological Aspect: The Pitfalls of Groupthink and How to Handle Them - Farkas, Johanna (Magyar Rendészet, 2016)
In the field of law enforcement coordinated work is the basis of professional efficiency. That is the reason why being acquainted with social psychological processes, which can serve as obstacles in group decision making, is a must. Sometimes group thinking is present in closely united groups or cases of great significance. In these situations, individuals tend to overrate the viewpoint held by the group as opposed to theirs in order to negotiate with consent. The decision-maker team can see the agreement as inviolable not letting criticism intrude. In extreme cases this can create capital errors in decision. By being familiar with the mechanisms that go with group thinking these errors could be avoided and possible mistakes be fixed.